Peningkatan Kompetensi Santri Ponpes Melalui Web Desain E-Marketing di Ponpes Al-Insan Kerotek Kecamatan Cibeber Kota Cilegon Banten - Arum Wahyuni Purbohastuti; Muhammad Johan Widikusyanto; Asmi Ayuning Hidayah; Didik Aribowo; Desmira Desmira; Ratna Ekawati (BANTENESE : JURNAL PENGABDIAN MASYARAKAT, 2021)
With these various advantages, it is necessary to further develop it to increase the income and welfare of the people in Islamic boarding schools which have the potential for managing economic empowerment with a large number of students. This of course requires assistance to the production and business management aspects of partners in each Islamic boarding school. Productive business institutions in Islamic boarding schools have complex institutional characteristics, so that the dynamics that occur between business actors greatly affect the performance of these productive businesses. This program is an empowerment activity for members of the “Insan Mandiri” Joint Business Group (KUB) of the Al Insan Kerotek Islamic Boarding School, Cibeber District, the output target to be achieved in this empowerment activity, namely the availability of intensively maintained productive efforts for Islamic boarding school students and the availability of the application of appropriate technology. simple activities in running productive businesses for joint business groups among students through web design training. The web design training method for students uses an open source web with simple steps for making it. It is hoped that this web design training can improve the competence of students in carrying out the promotion of the products of the students' work and business more optimally and are widely known by the public.